Corporate Governance in Air Asia Berhad - Muhammad Taufik, Mat Rais (Universiti Malaysia Pahang, 2017)
The aim of this paper is to discuss the corporate governance practice in Air Asia Berhad. Corporate governance is an important topic discussed in Malaysia as the government is fully supporting corporate governance issue by introducing the Malaysia Code of Corporate Governance (MCCG) for organizations in Malaysia to follow. Although there are issues on corporate governance failure appearing in the papers quite frequently, but there are also organizations that have a good corporate governance in place. This paper will discuss the corporate governance practice in one of Malaysia’s successful carrier. This paper first examines the level of corporate governance and its impact on firm performance which further branched out to board composition, financial disclosure and whistleblowing channel. Inside Air Asia Berhad, the author found that the organization fully complies with the recommendation of board composition plus they have a broad spectrum of board of directors with experience, expertise and reputation for integrity. Secondly, financial disclosure of Air Asia Berhad is fully transparent where all of the information is available in their website for investors to view and acquire. In addition, they have their own external auditors to ensure there is no manipulation of financial reports of the organizations. Thirdly, Air Asia Berhad have an internal whistle blowing channel which is delivered through email, contrasting with Dqorkin and Callahan (1993), stated that the best choice is external whistleblowing channel rather than internal as internal would create extensive form of retaliation to the employee from management. On the basis of the results of this research, it can be concluded that Air Asia Berhad, an organization in the airline industry takes corporate governance practice to its core and complying with the government effort on raising the corporate governance inside of Malaysia.